(3JaUjd GdfTCJjf hJMUjd GdSYGOJjfs - (3GdMSjf Hf eMeO Hf GdeaVd, CHh GdbGSe GdCUagGfj (B((3Ch GdCUHgGfj(B) (3GdeYQha HGdQGZH,J (B502 (3g` s
(3ChdgG (B:s
(3bJGd QMeI Gddg Ydjg gPg QSGdI aj JaUjd GdfTCJjf hJMUjd GdSYGOJjf GeG GdfTCJGf aGMOgeG GdePchQI aj bhdg JYGdi(B:" (3hdbO YdeJe GdfTCI GdChdi adhdG JPcQhf s
(3BNQgG (B:s
(3CYGffG Gddg Ydi HdhZ gPg GdOQLI hLYdfG ef GdoeJQTMjf dgG HQMeJg Efg Ydi eG jTGA bOjQ hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B46s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B255 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B59s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B462s
Keywords: (3GdJUha hGdBOGH GdTQYjIs